Respuesta :
Answer:
The solution would be (6, -11)
Step-by-step explanation:
In order to solve this system by substitution, simply take the value of y in the first equation and use it in place of y in the second. This will allow you to solve for x.
x = -2y - 16
x = -2(-3x + 7) - 16
x = 6x - 14 - 16
x = 6x - 30
-5x = -30
x = 6
Now that we have the value of x, we can find the value of y.
y = -3x + 7
y = -3(6) + 7
y = -18 + 7
y = -11
Answer:
Here is the break down of the answer x=6 and y=-11
Step-by-step explanation:
![Ver imagen marywdll](https://us-static.z-dn.net/files/d09/9b90b0be7766799e783a2ce51158aceb.png)